Comparative efficacy of hemorrhage control of a novel mesoporous bioactive glass versus two commercial hemostats. (8th February 2018) - Pourshahrestani, Sara; Kadri, Nahrizul Adib; Zeimaran, Ehsan; Gargiulo, Nicola; Samuel, Shani; Naveen, Sangeetha Vasudevaraj; Hasikin, Khairunnisa; Kamarul, Tunku; Towler, Mark R
Abstract: Mesoporous bioactive glass containing 1% Ga2 O3 (1%Ga-MBG) is attractive for hemorrhage control because of its surface chemistry which can promote blood-clotting. The present study compares this proprietary inorganic coagulation accelerator with two commercial hemostats, Celox TM (CX) and QuikClot Advanced Clotting Sponge Plus TM (ACS + ). The results indicate that the number of adherent platelets were higher on the 1%Ga-MBG and CX surfaces than ACS + whereas a greater contact activation was seen on 1%Ga-MBG and ACS + surfaces than CX. 1%Ga-MBG not only resulted in larger platelet aggregates and more extensive platelet pseudopodia compared to CX and ACS + but also significantly accelerated the intrinsic pathways of the clotting cascade. In vitro thrombin generation assays also showed that CX and ACS + induced low levels of thrombin formation while 1%Ga-MBG had significantly higher values. 1%Ga-MBG formed a larger red blood cell aggregate than both CX and ACS + . Direct exposure of 1%Ga-MBG to fibroblast cells increased cell viability after 3 days relative to CX and ACS +, inferring excellent cytocompatibility. The results of this study promote 1%Ga-MBG as a promising hemostat compared to the commercially available products as it possesses essential factors required for coagulation activation.